Emerging fluconazole resistance: Implications for the management of cryptococcal meningitis - Edward Mpoza; Joshua Rhein; Mahsa Abassi (Medical Mycology Case Reports, 2018)
We present the case of an HIV-seropositive individual with cryptococcal meningitis who was found to have a fluconazole resistant strain of Cryptococcus neoformans. The individual required multiple rounds of amphotericin and fluconazole 800–1200 mg after several episodes of clinical relapse. Cerebrospinal fluid sterilization was achieved and maintained with high doses of fluconazole. This case demonstrates the emerging dilemma of increasing rates of fluconazole resistance in Cryptococcus and the clinical difficulties in meningitis management.